Gut Microbiota Dysbiosis and Altered Bile Acid Catabolism Lead to Metabolic Disorder in Psoriasis Mice - Hao, Yan; Zhou, Pei; Zhu, Ya-juan; Zou, Song; Zhao, Qixiang; Yu, Jiadong; Hu, Yawen; Li, Jiong (Frontiers in Microbiology, 2022)
Patients with psoriasis tend to have significant comorbidities, such as hyperlipemia, diabetes mellitus and obesity, which belong to metabolic disorder. The specific mechanism that psoriasis increases metabolic disorder risk is uncertain. Here, we demonstrated that the dysbiotic gut microbiota of 6 months psoriasis-like model mice (K14-VEGF-A-transgenic) exacerbated psoriasis disease and induced metabolic disorder when transferred into 2 months mice. We confirmed by 16SrDNA gene sequencing that the Parabacteroides distasonis decreased in K14-VEGF mice with age, and P. distasonis also decreased in the transferred mice. Metabolomic screening identified an altered bile acid profile, including a decrease in chenodeoxycholic acid (CDCA) in the feces of transferred mice. Additionally, CDCA supplement prevented metabolic disorder in K14-VEGF-A-transgenic mice. Consequently, we found that aberrant bile acid metabolism may contribute to metabolic disorder in K14-VEGF-A-transgenic mice, indicating the possibility to prevent and treat the metabolic disorder by targeting gut microbial metabolites in psoriasis mice.